(untitled) (Confluenţe Bibliologice, 2025)
Radu Motoc, Honorary Member of the Senate, engineer from Galati presents the books of Oana Marinache, an art critic, president of the Association of History and Art Publishing House. The publications have recently appeared in a collection entitled: Architects forget. Launching of works was held within the international symposium „Tradition and Future, a Monument” in Iasi in 2015, in which the author herself presented several volumes in a special room in the Palace of Culture.